Solvothermal synthesis of Bi2S3 nanoparticles and nanorods towards solar cell application - Arumugam, J. (2019)
One-dimensional nanostructures have gained more attraction in recent years because of their high aspect ratio. Uniform Bi2S3 nanorods have been grown using N,N-dimethylformamide (DMF) and ethylene glycol (EG) as solvents by solvothermal method, inorder to study the effect of solvent on the properties of the prepared Bi2S3. Also, the reaction temperature has been changed to examine its role in tuning the property of the Bi2S3 nanorods. The x-ray diffraction (XRD) results show that the Bi2S3 nanorods are of orthorhombic phase. The high resolution scanning electron microscope (HRSEM) and high resolution transmission electron microscope (HRTEM) studies reveal the appearance of rod-like structures with the typical length in the range of 1 µm and average diameter is around 150 nm. The solvent effects and reaction temperatures are discussed in detailed. The band gap of the prepared samples have been estimated using Tauc plot and this suggests that the prepared Bi2S3 nanostructures may find potential applications in the fabrication of solar cells.